CONTEXTUAL-BASED MODULE VALIDATION TEST INTEGRATING CREATIVE THINKING ABILITY IN STATIC FLUID MATERIALS, TEMPERATURE AND HEAT IN CLASS XI SMA/MA - Vira Melodia Savitri; - Hufri; - Akmam; Silvi Yulia Sari; Fanny Rahmatina Rahim (Universitas Negeri Padang, 2022)
Responding to the 21st century, among others, is necessary to develop creative thinking skills. However, students' creative thinking skills are still low, this is due to the lack of modules that can help students in their knowledge and develop creative thinking skills, including in physics subjects. In general, this researcher is producing a contextual-based physics module that integrates creative thinking skills. In this research, the type used is R&D with ADDIE design. The instruments are in the form of a validity test questionnaire sheet by the lecturer and a practicality test questionnaire sheet by the lecturer. Furthermore, the data were analyzed using statistics with a correlated t-test”. Based on the analyzed data, it shows that the physics module developed has a value of 84.80 and is in the valid category. The use of the module on static fluid and heat temperature values obtains practicality values of 88 and 92, respectively, both of which are in the practical category. The use of the tested module its effectiveness on high school students scored 30.33 at the pretest stage and 60.73 at the posttest stage. This increase indicates that the module is in the effective category.